Reduced monocyte adhesion to aortae of diabetic plasminogen activator inhibitor-1 knockout mice - Zhao, Ruozhi; Le, Khuong; Moghadasian, Mohammed H.; Shen, Garry X. (Inflammation research, 2017)
Objective and design To determine the requirement of plasminogen activator inhibitor-1-knockout (PAI-1) for monocyte adhesion in animals and cells under diabetic conditions. Methods and subjects Monocyte adhesion assay, enzyme-linked immunosorbent assay, and Western blotting were used in analyzing samples from PAI-1-knockout (PAI-1-KO) mice or cultured human umbilical vein endothelial cells (HUVEC). Treatments Diabetes in PAI-1-KO and wild-type mice was induced by intraperitoneal injection of streptozotocin (STZ). HUVEC was transfected with short interference RNA (siRNA) against PAI-1, tumor necrosis factor-α (TNFα), or toll-like receptor (TLR4), and then was treated with glycated low-density lipoproteins (glyLDL). Results The adhesion of monocytes to aortic intima was reduced in PAI-1-KO mice, which was associated with decreased levels of TNFα and monocyte chemotactic protein-1 (MCP-1) in plasma and cardiovascular tissue, and increased abundances of urokinase plasminogen activator (uPA) and uPA receptor (uPAR) in cardiovascular tissue compared to wild-type mice. Significant reductions in monocyte adhesion, inflammatory, and fibrinolytic regulators were detected in cardiovascular tissue or plasma in diabetic PAI-1-KO mice compared to wild-type diabetic mice. Transfection of PAI-1, TNFα or TLR4 siRNA to HUVEC inhibited glyLDL-induced monocyte adhesion to EC. PAI-1 siRNA inhibited the abundances of TLR4 and TNFα in EC. Conclusion The findings suggest that PAI-1 is required for diabetes-induced monocyte adhesion via interactions with uPA/uPAR, and it also regulates TLR4 and TNFα expression in vascular EC. Inhibition of PAI-1 potentially reduces vascular inflammation under diabetic condition.